Resting state connectivity patterns with near-infrared spectroscopy data of the whole head - Novi, Sergio L. (Biomed Opt Express, 2016)
Resting state cerebral dynamics has been a useful approach to explore the brain’s functional organization. In this study, we employed graph theory to deeply investigate resting state functional connectivity (rs-FC) as measured by near-infrared spectroscopy (NIRS). Our results suggest that network parameters are very similar across time and subjects. We also identified the most frequent connections between brain regions and the main hubs that participate in the spontaneous activity of brain hemodynamics. Similar to previous findings, we verified that symmetrically located brain areas are highly connected. Overall, our results introduce new insights in NIRS-based functional connectivity at rest.